Fluorescence Lifetime Imaging and Spectroscopic Co-Validation for Protoporphyrin IX-Guided Tumor Visualization in Neurosurgery - Reichert, David; Erkkilae, Mikael T.; Gesperger, Johanna; Wadiura, Lisa I.; Lang, Alexandra; Roetzer, Thomas; Woehrer, Adelheid; Andreana, Marco; Unterhuber, Angelika; Wilzbach, Marco; Hauger, Christoph; Drexler, Wolfgang; et al. (Frontiers in Oncology, 2021)
Maximal safe resection is a key strategy for improving patient prognosis in the management of brain tumors. Intraoperative fluorescence guidance has emerged as a standard in the surgery of high-grade gliomas. The administration of 5-aminolevulinic acid prior to surgery induces tumor specific accumulation of protoporphyrin IX, which emits red fluorescence under blue-light illumination. The technology, however, is substantially limited for low-grade gliomas and weakly tumor infiltrated brain, where low protoporphyrin IX concentrations are outweighed by tissue autofluorescence. In this context, fluorescence lifetime imaging has shown promise to distinguish spectrally overlapping fluorophores. We integrated frequency-domain fluorescence lifetime imaging in a surgical microscope and combined it with spatially registered fluorescence spectroscopy, which can be considered a research benchmark for sensitive protoporphyrin IX detection. Fluorescence lifetime maps and spectra were acquired for a representative set of fresh ex-vivo brain tumor specimens (low-grade gliomas n=15, high-grade gliomas n=80, meningiomas n=41 and metastases n=35). Combining the fluorescence lifetime with fluorescence spectra unveiled, how weak protoporphyrin IX accumulations increased the lifetime respective to tissue autofluorescence. Infiltration zones (4.1ns±1.8ns, p=0.017) and core tumor areas (4.8ns±1.3ns, p=0.040) of low-grade gliomas were significantly distinguishable from non-pathologic tissue (1.6ns±0.5ns). Similarly, fluorescence lifetimes for infiltrated and reactive tissue as well as necrotic and core tumor areas were increased for high-grade gliomas and metastasis. Meningioma tumor specimens showed strongly increased lifetimes (12.2ns±2.5ns, p=0.005). Our results emphasize the potential of fluorescence lifetime imaging to optimize maximal safe resection in brain tumors in future and highlight its potential towards clinical translation.